Analysis of the clinical efficacy of laparoscopic middle pancreatectomy in the treatment of benign or low-grade malignant tumors of the pancreas - Liao, Yan; Zhou, Wei; Dai, Manxiong; Zhou, Jie; Wang, Yi; He, Xiangyu; Liu, Yi; Cheng, Wei (Frontiers in Oncology, 2023)
Objective The aim of this study was to investigate the clinical efficacy of laparoscopic middle pancreatectomy in the treatment of benign and junctional tumors of the pancreas. Methods Retrospective analysis of basic data, tumor diameter, statistical analysis, and evaluation of efficacy-related indicators such as operative time, intraoperative bleeding, pathological findings, postoperative hospital stay, postoperative pancreatic fistula incidence, and pancreatic endocrine function was carried out on 17 patients diagnosed with benign or low-grade malignant tumors of the pancreas and laparoscopic middle pancreatic resection from January 2018 to January 2023 at the First Affiliated Hospital of Hunan Normal University. Results A total of 17 patients were screened. There were eight males and nine females; mean age was 42.8 ± 17.4 years (range: 15–69 years); BMI was 22.6 ± 2.5 kg/m2 (range: 18.4–27.5 kg/m2), and the tumor size was 3.4 ± 1.2 cm (range: 1.5–5.5 cm). Preoperative glycan antigen CA19-9 was negative and CA125 was negative. Surgical time was 393.2 ± 57.9 min; intraoperative bleeding was 211.7 ± 113.9 ml; tumor diameter size was 3.4 ± 1.2 cm; postoperative admission time was 19.4 ± 7.6 days; postoperative pancreatic fistula (POPF) grading was 17 cases, including nine cases of A-grade fistula, three cases of B-grade fistula, and none of C-grade fistula; postoperative pathology results were five cases of plasmacytoma, three cases of mucinous cystadenoma, four cases of SPN (solid pseudopapillary neoplasm), one case of Intraductal Papillary Mucinous Neoplasm (IPMN), three cases of pancreatic Neuroendocrine Neoplasm (pNEN), one case of inflammatory myofibroblastic osteoblastoma. All cases did not develop pancreatic origin diabetes or exacerbation of previous diabetes, and no cases presented symptoms of exocrine insufficiency such as dyspepsia and diarrhea. Conclusion Laparoscopic middle pancreatectomy is safe and feasible in the treatment of benign or low-grade malignant tumors in the body of the pancreatic neck and is not accompanied by increased risk of intraoperative and postoperative complications and endocrine dysfunction of the pancreas.